Indonesian Presidential Election on Presidential Threshold Policy: Evidence from Various Countries - Siboy, Ahmad; Sholahuddin Al-Fatih (Lembaga Contrarius Indonesia, 2025)
The study develops a constitutional design to regulate the number of presidential and vice-presidential candidates following the Constitutional Court’s annulment of the presidential threshold. It observes that the absence of a model framework from the Court creates a regulatory vacuum that may expose the presidential election to political fragmentation, heightened polarization, and procedural inefficiencies. To address this issue, the research aims to construct a constitutional framework capable of enhancing electoral stability while sustaining democratic competitiveness. The study employs a normative juridical method supported by statutory analysis, case studies, and comparative assessment to identify feasible regulatory alternatives. The analysis demonstrates that the most effective approach to limiting the number of candidates is to regulate the number of political parties eligible to participate in general elections, given their role as the primary gatekeepers of nomination. The findings propose several regulatory instruments, including a moratorium on the establishment of new political parties, stricter requirements for party formation, enhanced eligibility criteria for electoral participation, a minimum age requirement for political parties, a maximum threshold for the number of qualified parties, and the disqualification of previously registered parties that fail to meet revised standards. The study concludes that these mechanisms collectively form a coherent constitutional strategy for maintaining a manageable number of presidential candidates and ensuring the continuity, integrity, and effective governance of the electoral process.